2021
DOI: 10.1186/s40659-021-00342-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecules linked to Ras signaling as therapeutic targets in cardiac pathologies

Abstract: The Ras family of small Guanosine Triphosphate (GTP)-binding proteins (G proteins) represents one of the main components of intracellular signal transduction required for normal cardiac growth, but is also critically involved in the development of cardiac hypertrophy and heart failure. The present review provides an update on the role of the H-, K- and N-Ras genes and their related pathways in cardiac diseases. We focus on cardiac hypertrophy and heart failure, where Ras has been studied the most. We also revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 113 publications
(243 reference statements)
1
22
0
Order By: Relevance
“…Within the RAS system, the ACE2/Ang 1–7/Ang 1–9/MasR axis counterposes the ACE1/Ang II/AT1 receptor axis. With a homologous catalytic domain as for ACE1, ACE2 competes with ACE1 to convert Ang II to Ang 1–7 and Ang 1–9, which provides anti-vasoconstrictive, anti-inflammatory, anti-hypertrophic, and antifibrotic effects on various tissue including the cardiomyocytes by inhibiting NFAT [ 25 , 26 ]. Thus, inhibiting the RAS and activating the counterbalancing ACE2/Ang 1–7/Ang 1–9/MasR axis might have complementary action in cardiovascular diseases, including heart failure progression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the RAS system, the ACE2/Ang 1–7/Ang 1–9/MasR axis counterposes the ACE1/Ang II/AT1 receptor axis. With a homologous catalytic domain as for ACE1, ACE2 competes with ACE1 to convert Ang II to Ang 1–7 and Ang 1–9, which provides anti-vasoconstrictive, anti-inflammatory, anti-hypertrophic, and antifibrotic effects on various tissue including the cardiomyocytes by inhibiting NFAT [ 25 , 26 ]. Thus, inhibiting the RAS and activating the counterbalancing ACE2/Ang 1–7/Ang 1–9/MasR axis might have complementary action in cardiovascular diseases, including heart failure progression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK signaling is directly involved in the progression of ventricular dysfunction, because it promotes cardiomyocyte adaptation to different stressors, which in turn triggers mechanisms of cardiac inflammation and further stimulates fibrosis [ 14 , 15 , 46 , 47 ]. Cardiac activation of caspase-3 leads to an ongoing apoptotic process in RV tissue in PH rats, indicating a transitioning to failing phenotype in RV myocytes [ 16 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic changes in Ras isoforms or genes in the Ras‐MAPK pathway also lead to heart disease. 26 , 27 Lin et al 28 found that silencing miR‐665 restored cardiac function in rats with heart failure through the cAMP signaling pathway and overexpression of GLP1R. Qin et al 29 found that overexpressing miR‐22‐5p altered the miR‐22‐5p target gene Rap1a and the RAP1/ERK signaling pathway and affected the progression of myocardial injury.…”
Section: Discussionmentioning
confidence: 99%
“…The Ras family of small guanosine triphosphate‐binding proteins in the Ras signaling pathway is essential for intracellular signal transduction for cardiac growth and is involved in the development of cardiac hypertrophy and heart failure. Genetic changes in Ras isoforms or genes in the Ras‐MAPK pathway also lead to heart disease 26,27 . Lin et al 28 found that silencing miR‐665 restored cardiac function in rats with heart failure through the cAMP signaling pathway and overexpression of GLP1R.…”
Section: Discussionmentioning
confidence: 99%